Does an Invasive Bivalve Outperform Its Native Congener in a Heat Wave Scenario? A Laboratory Study Case with Ruditapes decussatus and R. philippinarum - Crespo, Daniel (2021)
Global warming and the subsequent increase in the frequency of temperature anomalies are expected to affect marine and estuarine species' population dynamics, latitudinal distribution, and fitness, allowing non-native opportunistic species to invade and thrive in new geographical areas. Bivalves represent a significant percentage of the benthic biomass in marine ecosystems worldwide, often with commercial interest, while mediating fundamental ecological processes. To understand how these temperature anomalies contribute to the success (or not) of biological invasions, two closely related species, the native Ruditapes decussatus and the introduced R. philippinarum, were exposed to a simulated heat wave. Organisms of both species were exposed to mean summer temperature (~18 °C) for 6 days, followed by 6 days of simulated heat wave conditions (~22 °C). Both species were analysed for key ecological processes such as bioturbation and nutrient generation-which are significant proxies for benthic function and habitat quality-and subcellular biomarkers-oxidative stress and damage, and energetic metabolism. Results showed subcellular responses to heat waves. However, such responses were not expressed at the addressed ecological levels. The subcellular responses to the heat wave in the invasive R. philippinarum pinpoint less damage and higher cellular energy allocation to cope with thermal stress, which may further improve its fitness and thus invasiveness behaviour.